Erratum: Electrocaloric cooling: The importance of electric-energy recovery and heat regeneration. (21st October 2015) - Plaznik, U.; Vrabelj, M.; Kutnjak, Z.; Malič, B.; Poredoš, A.; Kitanovski, A.
Abstract: Original article: EPL, 111 (2015) 57009 .